Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1103/physrevb.101.134303
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent lattice dynamics of antiferromagnetic and ferromagnetic phases of FeRh

Abstract: We have investigated lattice dynamics of antiferromagnetic and ferromagnetic phases of cubic (B2) FeRh at various temperatures from first principles using the temperature-dependent effective potential method. We have shown that already at low temperature the cubic structure of the antiferromagnetic phase becomes dynamically stable, which eliminates the contradiction between experimental observations and previous theoretical results showing its dynamical instability at temperature T = 0 K. In addition, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…The observation of the FOMT at temperatures close to the temperature of the human body in these alloys, in combination with a giant MCE [14], make Fe-Rh-based materials promising for use in areas less sensitive to the cost of the alloy, primarily in medicine (for example, in the technology of targeted drug delivery [15,16]), magnetic recording [17], etc. In the majority of works studying the origin of the magnetic phase transition in ironrhodium alloys, attention focused on various energy contributions to the free energy: phonon, conduction electron and magnons [18], exchange energy associated with magneto-volume effects [19], and lattice dynamics [20], which can be clarified by direct observation of the phase transformation [21]. At the same time, the influence of phase coexistence on the functional properties of the material is much less studied, except for a few works on thin films: see examples of Fe 49 Rh 51 [22] and FeRh 0.82 Pd 0.18 [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation of the FOMT at temperatures close to the temperature of the human body in these alloys, in combination with a giant MCE [14], make Fe-Rh-based materials promising for use in areas less sensitive to the cost of the alloy, primarily in medicine (for example, in the technology of targeted drug delivery [15,16]), magnetic recording [17], etc. In the majority of works studying the origin of the magnetic phase transition in ironrhodium alloys, attention focused on various energy contributions to the free energy: phonon, conduction electron and magnons [18], exchange energy associated with magneto-volume effects [19], and lattice dynamics [20], which can be clarified by direct observation of the phase transformation [21]. At the same time, the influence of phase coexistence on the functional properties of the material is much less studied, except for a few works on thin films: see examples of Fe 49 Rh 51 [22] and FeRh 0.82 Pd 0.18 [23].…”
Section: Introductionmentioning
confidence: 99%
“…The most recent theoretical work to date, which addresses the issue of phase co-existence, is [20]. The lattice dynamics of the antiferromagnetic and ferromagnetic phases of FeRh at different temperatures were investigated from first principles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the seminal time-resolved X-ray diffraction experiment of Mariager et al 32 and recent theoretical predictions 34 of a significant difference in the expected temperature dependence of lattice vibrations of the FM and AF phases, we performed a X-FEL based time-resolved experiment to determine the FeRh AF and lattice dynamics on the sub-ps time scale, at an X-ray energy of 6.408 keV.…”
Section: Resultsmentioning
confidence: 99%
“…By measuring TR-XRD, it is possible to monitor the changes that occur to the FeRh lattice after laser excitation and ascertain the presence of transient states on time scales dictated by the excitation laser pulse duration. Extending these measurements beyond the reports of Mariager et al 32 is particularly appealing since recent simulations 6 , 33 , 34 of FeRh phonon bands using density functional theory (DFT) have revealed that the lattice dynamics plays a decisive role in the meta-magnetic phase transition, reflected in a significant difference in the expected temperature dependence of lattice vibrations of the ferromagnetic and antiferromagnetic phases.…”
Section: Introductionmentioning
confidence: 99%